Arginase: The Emerging Therapeutic Target for Vascular Oxidative Stress and Inflammation - Yang, Zhihong; Ming, Xiu-Fen (Frontiers in Immunology, 2013)
Oxidative stress and inflammation in the vascular wall are essential mechanisms of atherosclerosis and vascular dysfunctions associated with risk factors such as metabolic diseases, aging, hypertension, etc. Evidence has been provided that activation of the vascular endothelial cells in the presence of the risk factors promotes oxidative stress and vascular inflammatory responses, leading to acceleration of atherosclerotic vascular disease. Increasing number of studies from recent years demonstrates that uncoupling of endothelial nitric oxide synthase (eNOS), whereby the enzyme eNOS produces detrimental amount of superoxide anion O2.– instead the vasoprotective nitric oxide (NO.), plays a critical role in vascular dysfunction under various pathophysiological conditions and in aging. The mechanisms of eNOS-uncoupling seem multiple and complex. Recent research provides emerging evidence supporting an essential role of increased activity of arginases including arginase-I and arginase-II in causing eNOS-uncoupling, which results in vascular oxidative stress and inflammatory responses, and ultimately leading to vascular diseases. This review article will summarize the most recent findings on the functional roles of arginases in vascular diseases and/or dysfunctions and the underlying mechanisms in relation to oxidative stress and inflammations. Moreover, regulatory mechanisms of arginases in the vasculature are reviewed and the future perspectives of targeting arginases as therapeutic options in vascular diseases are discussed.